The Effectiveness of Organizational Communication of Islamic Bank of North Sumatra in Increasing Public Interest in Savings in Binjai City - Melati Muslim; Mailin Mailin; Hasnun Jauhari Ritonga (Budapest International Research and Critics University, 2022)
This study aims to explain the effectiveness of the organizational communication of the Islamic Bank of North Sumatra in increasing public interest in saving in Binjai City, including explaining the obstacles and explaining the results of the effectiveness of the organizational communication of the Islamic Bank of North Sumatra in increasing public interest in saving, especially at the North Sumatran Syariah Bank of Binjai City. Individual Difference Theory, Social Relationship Theory, and Interpersonal Theory are some of the theoretical foundations in this research which uses a descriptive qualitative research approach through data collection techniques such as interviews and observations. Constraints faced by the organization of the Islamic Bank of North Sumatra in communicating the products of the Bank of North Sumatra are the lack of complete information about the products of the Islamic Bank of North Sumatra and there are no funds for saving. The results of the research on the effectiveness of the organizational communication of Bank Sumut Syariah in increasing public interest in saving in Binjai City, namely, showing that in carrying out the process of increasing public interest in saving in Binjai City, the organization of Bank Sumut Syariah or marketing of Bank Sumut Syariah uses structured sales steps to attract interest people save, the face-to-face method or going directly to their customers shows high results in communicating, because one hundred percent of the customers encountered by marketing use this method.